Обґрунтування бренд-стратегії розвитку хлібопекарської галузі у Причорноморському регіоні - Майборода, Ганна Олександрівна; Майборода, Анна Александровна; Maiboroda, Hanna (My University, 2021)
UK: У статті розглянуто використання такого маркетингового інструменту, як бренд-стратегія, для підвищення конкурентоспроможності підприємств хлібопекарської галузі Причорноморського регіону. Хлібопекарська галузь є однією зі стратегічно важливих ланок ринкової економіки держави, вона формує продовольчу безпеку країни. Але підприємства галузі стикаються з певними зовнішніми проблемами, які мають істотний вплив на їхню діяльність. Для запобігання цим негативним чинникам та зниження їхнього впливу у роботі запропоновано створення економічно обґрунтованої бренд-стратегії для підприємств галузі, яка покликана формувати цілісне сприйняття бренду у свідомості споживача, створювати позитивні враження від використання, спонукати до придбання. У сучасній науковій практиці для аналізу конкурентоспроможності підприємств використовують різні економічні методи. За допомогою матричного методу, а саме складання матриці McKinsey/General Electric, виявлено й оцінено критерії конкурентоспроможності та привабливості основних хлібопекарських виробників Причорноморського регіону. На основі висновків, які отримані під час проведення дослідження, кожному підприємству було запропоноване використання певної стратегії щодо розвитку бренду та збільшення конкурентоспроможності на ринку. RU: В статье рассмотрено использование такого маркетингового инструмента, как бренд-стратегия, для повышения конкурентоспособности предприятий хлебопекарной отрасли Причерноморского региона. Хлебопекарная отрасль является одним из стратегически важных звеньев рыночной экономики государства, она формирует продовольственную безопасность страны. Но предприятия отрасли сталкиваются с определенными внешними проблемами, которые оказывают существенное влияние на их деятельность. Для предотвращения этих негативных факторов и снижения их влияния в работе предложено создание экономически обоснованной бренд-стратегии для предприятий отрасли, которая призвана формировать целостное восприятие бренда в сознании потребителя, создавать положительные впечатления от использования, побуждать к приобретению. В современной научной практике для анализа конкурентоспособности предприятий используют различные экономические методы. С помощью матричного метода, а именно составления матрицы McKinsey/General Electric, выявлены и оценены критерии конкурентоспособности и привлекательности основных хлебопекарных производителей Причерноморского региона. На основе выводов, полученных при проведении исследований, каждому предприятию было предложено использование определенной стратегии по развитию бренда и увеличения конкурентоспособности на рынке. EN: The article considers the use of such a marketing tool as a brand strategy to increase the competitiveness of bakery enterprises in the Black Sea region. The bakery industry is one of the strategically important parts of the market economy of the state, it forms the food security of the country. But enterprises in the industry face certain external problems that have a significant impact on their activities, such as instability and constant changes in the external environment, increased competition at the national and global levels, reduced production due to reduced purchasing power. To prevent these negative factors and reduce their impact, this paper proposes the creation of an economically sound brand strategy for enterprises in the industry, which aims to form a holistic perception of the brand in the minds of consumers, create positive impressions of use, encourage acquisition. In modern scientific practice, various economic methods are used to analyze the competitiveness of enterprises. In the study, a matrix method was used to form a brand strategy by assessing competitiveness. The McKinsey / General Electric matrix (competitiveness-attractiveness matrix) is a multifactor model consisting of 9 squares and characterizing the long-term attractiveness of the industry and the company's competitive position in it. Advantages of its use: validity (does not lead to simplified conclusions), flexibility (factors are selected according to the specific market situation), breadth of application. Disadvantages include: difficulties and subjectivity in determining the weight of a particular factor, recommendations and conclusions based on it are general in nature and need clarification. As a result of compiling the McKinsey matrix, it was found that the leading bakery enterprises in the Black Sea region occupy high positions. It was proposed to use the strategy of maintaining leadership, make maximum investments in the development of promising products, expand the range through the use of alternative ingredients, increase profitability by increasing productivity, develop the brand, use modern Internet technologies.
Brand-strategic rationale for the development of the bakery industry in the Black Sea region
Keywords: бренд-стратегія; бренд; бренд-менеджмент; хлібопекарська галузь; конкурентоспроможність; матриця McKinsey; Причорноморський регіон; бренд-стратегия; хлебопекарная отрасль; конкурентоспособность; матрица McKinsey; Причерноморский регион; brand strategy; brand; brand management; bakery industry; competitiveness; McKinsey matrix; Black Sea region